Facility, Location and Employer – Employee Relations of German-Canadian Businesses in Canada - Eiselt, H.; Eiselt, Marianne (Journal of Comparative International Management, 2014)
The purpose of this paper is an investigation into aspects of the decision-making process of German-Canadian business owners regarding the reasons for their choice of location and their assessment of the differences of some major traits of German and Canadian employees. This paper presents the results of a questionnaire that was administered by mail to German business owners in Canada. The purpose of this focus is to provide regional planners with some understanding why German owners/managers choose specific provinces or sites, and to provide managers in Canada with information concerning differences in traits of German and Canadian employees. The results of this work are that location decisions are mostly personal when it comes to choosing Canada as a country for their business, but the more we zoom into the chosen province and the specific site, the more business-related features become relevant. As far as personnel evaluations by German managers are concerned, the key result is that while at first glance it may appear that Canadians and Germans (and, by extension, Canadian and German employees) are not very different culturally, they actually are. Whereas some results appear to support common stereotypes, e.g., Canadians rank higher when it comes to politeness and tolerance, while Germans excel in job knowledge and punctuality, others are more unexpected. Among them are the results indicating no significant differences when it comes to flexibility, ambitiousness, and the acceptance of authority.